Electrospun Nitrogen‐Doped Carbon Nanofibers Encapsulating Cobalt Nanoparticles as Efficient Oxygen Reduction Reaction Catalysts. Issue 9 (19th July 2016) - Shang, Chaoqun; Li, Minchan; Wang, Zhenyu; Wu, Shaofei; Lu, Zhouguang
Abstract: The development of low‐cost, high‐performance, nonprecious‐metal electrocatalysts for the oxygen reduction reaction (ORR) is highly desirable to reduce the cost of fuel systems. Self‐supported nitrogen‐doped carbons containing cobalt have been developed by electrospinning followed by pyrolysis treatment. Polyacrylonitrile (PAN) with abundant carbon and nitrogen sources serves as a polymer in the fabrication of one‐dimensional nanofibers by electrospinning. After being calcined at various temperatures, the obtained nitrogen‐doped carbon nanofiber encapsulating cobalt nanoparticles at 800 °C (Co‐PAN‐800) exhibits the highest ORR activity with onset and half‐wave potentials of −0.02 and −0.092 V (vs. Hg/HgO) in 0.1 m KOH, respectively. Additionally, the optimal Co‐PAN‐800 material shows remarkable stability and strong tolerance against methanol crossover. The promising ORR performance of Co‐PAN‐800 is attributed to the high surface area (407.43 m 2  g −1 ), which ensures sufficient exposure of electrocatalytically active sites. XPS analysis further demonstrates that pyrrolic nitrogen and a highly graphitized carbon structure may be responsible for the enhanced ORR activity of Co‐PAN‐800; cobalt may be involved in the creation of pyrrolic nitrogen during pyrolysis treatment. Abstract : Temperature adjustment : Nitrogen‐doped carbon nanofibers composed of polyacrylonitrile (PAN) calcined at different temperatures encapsulate cobalt nanoparticles. Cobalt nanoparticles are distributed throughout the fiber framework (see figure). The electrocatalyst calcined at 800 °C shows comparable oxygen reduction reaction performance to that of commercial Pt/C.